Izvlečki iz slovenske "romologije" - Komac, Miran (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2005)
The article highlights the attitude of the Slovene state authorities towards Roma, with special emphasis on their criminality in the first decade following the World War II. Roma were not acknowledged as a special ethnic community; they were treated as a foreign intruder into the Slovene national body and as a population hard to integrate into the Slovene society. All the attempts on the part of the Slovene society to solve the Roma problem (which were neither systematic nor long-term) failed to bring favourable results. Dueto instability, vagrancy, bungling and thefts Roma often found themselves persecuted by police and law courts. The biggest legal trial against Roma charged with a number of criminal offences was carried out the District Court of Maribor in 1952. A group of Roma were sentenced to yearlong imprisonment, three of them even to death. The article also deals with rather unusual relations between Roma and the majority population. It's true that Roma committed a number of thefts, but they were just a link in the trafficking chain, where profits mostly went to majority population. What's more, due to their in-born criminality, Roma were accused of criminal acts, committed by members of the majority nation. With scapegoat at hand, there is no point in wasting time and state money for in-depth investigations. The article ends with a note on sexual abuse of Roma girls.
Keywords: Slovenia; Slovenija; Romi; diskriminacija; kriminogenost; povojno obdobje